The Relationship Between Parenting and Video Games of Addiction Trends During COVID-19 Pandemic in Adolescents at Muhammadiyah 1 Senior High School Yogyakarta - Windy Aristiani; Wirasto , TR; Ismanto , HS (Universitas Ahmad Dahlan, 2023)
The COVID-19 pandemic has had an impact on school closures and social distancing. Teenagers spend time playing video games to overcome boredom, as a result, teenagers are increasingly attached to video games so they are at risk of experiencing addiction that has a negative impact on behavior and social. Parenting patterns determine and prevent the risk of video game addiction in adolescents. The three types of parenting are authoritarian, democratic, and permissive. Choosing the wrong parenting style can increase the risk of video game addiction in adolescents. This research is a non-experimental, descriptive-analytic with a cross-sectional approach. The research subjects were students of first-grade SMA Muhammadiyah 1 Yogyakarta. GAS was an instrument to measure game addiction. PAQ was an instrument to measure parenting style. Total of the research subjects 168, 7 subjects were excluded, and 161 subjects were obtained who play video games with authoritarian parenting 21 (13.0%), permissive 14 (8.7%), and democratic 126 (78.3%). There is a significant relationship between parenting styles and tendencies toward video game addiction (x2=13.17, p=0.001, C=0.275). Type of parenting authoritarian, permissive, and gender has a significant effect on the tendency of video game addiction, with (OR=6.05 for authoritarian, OR=6.3 for permissive, and OR=5.3 for gender). There is a significant relationship between parenting style and the tendency of video game addiction in adolescents at SMA Muhammadiyah 1 Yogyakarta. Authoritarian and permissive, as well as gender are the most influential factors in the behavior of video game addiction tendencies in teenagers at SMA Muhammadiyah 1 Yogyakarta.